The Effect of Heating on Ascorbic Acid Levels of Brassica oleracea L. Determined by UV-Visible Spectrophotometry - Muzakkir Baits; Riski Mentari Jahri; Asriani Suhaenah; Aminah Aminah; Tadjuddin Naid; Muammar Fawwaz (Pharmaceutical Reports, 2022)
Vitamin C is one of the nutrients that act as antioxidants derived from fruits and green vegetables, such as the broccoli (Brassica oleracea L.). This study aims to warming influence on levels of vitamin C in broccoli (Brassica oleracea L.) with qualitative and quantitative analysis. Qualitative analysis was performed using specific reagents that ammonium molybdate, Fehling Fehling's A and B which have indicated a positive sample containing vitamin C, and vitamin C were analyzed quantitatively using UV- Vis spectrophotometry at a wavelength of 570 nm. The results showed levels of vitamin C in raw broccoli 0.62915 mg/g and steamed broccoli 0.45449 mg/g.